Analytical model for the moisture absorption in capillary active building materials. (December 2017) - Janetti, Michele Bianchi; Wagner, Peter
Abstract: Isothermal absorption of moisture in a semi-infinite porous body is described with a diffusion law as a free boundary problem in which the porous domain is divided into a nearly saturated and a nearly dry region. This problem is solved via an analytical approach by assuming the diffusivity as a step function of the volumetric water content. The analytical solution is then applied to modeling the behavior of two real building materials during a water uptake test. It is shown that the model is able to explain the absorption process adequately, and that a good agreement with the measured data is obtained. Finally, a novel method for the inverse determination of the diffusivity via water uptake tests is proposed. Highlights: An analytical model describing the moisture absorption in a capillary building material is proposed. A closed form equation relating the water uptake coefficient to the diffusivity is derived. A good agreement with the measured data and with a numerical solution is found. A novel method for the inverse determination of the diffusivity is proposed.